Oficinas: a criação de estratégias na educação de surdos - Berned, Igor da Silveira (2014)
The self-training movement of a teacher creating education workshop strategies (CORREA, 2000 & 2006) potentiated a research development with an interest of map the acquired knowledge during the immersion on deaf science education, on Escola Estadual de Educação Especial Doutor Reinaldo Fernando Coser, in Santa Maria/RS. The focus of this study is to report through diary and notes the reflection movements of a teacher in front of the question how should a science concept be shown if there is no signal in LIBRAS? The notes were produced during a science teacher training and on workshop realized through the extension project at school during the Chemistry Graduation. These writings shows an estrangement on teachers formation that is comprehend with the subjectivity machine of a teacher body (CORREA & PREVE, 2011) which the effect is exhaustion of teacher capacity to create different strategies of study to answer tests . In this cartography (ROLNIK, 2007) (GUATARRI & ROLNIK, 2011) the science education with deaf is comprehend such as a study territory (FREIRE, 1988) in know process with will (STIRNER, 2001). And giving a language (ROLNIK, 2007) to these sensations present on the diary notes grow such as a necessity of speak what still has not been said to Natural Science teachers. Giving space to visualization of these notes allowing find the acquired knowledge from bifurcation realized by the teacher in front of his questions which compose his self-training process.